The Relationship between Age and Husband's Support for Pregnant Women on the Prevention of Baby Blues in PMB Azimah, Jambi City - Syafma, Nidi Kurnia; Haryanti, Dwi; Ningsih, Nisa Kartika; Mariana, Silvia (Journal of Education Technology Information Social Sciences and Health, 2024)
According to data from the Center for Diseases Control from 2004-2021, the prevalence of postpartum depression was 11.5% from 27 countries (Rockhill et al, 2017). The incidence of postpartum depression in Asia is quite high and varies between 3.5% to 63.3% (Yusuff ASM et al, 2015). According to the Ministry of Health (2019), it explains that Baby blues syndrome or postpartum stress, is a very mild form of depression which usually occurs in the first 14 days after giving birth and tends to get worse around the third or fourth day after giving birth. Almost all mothers who have just given birth experience baby blues. This study aims to determine the relationship between age and husband's support for pregnant women on the prevention of baby blues in PMB Azimah, Jambi City. This research uses a quantitative type of research with a cross sectional research design. The population in this study was 354 pregnant women who checked for pregnancy from January to March 2023 at PMB Azimah, Jambi City. The sampling technique was simple random sampling technique with a total sample of 35 pregnant women. Data analysis used the Chi-Square test. The research results showed that most of the known ages of pregnant women in PMB Azimah, Jambi City who were at risk were categorized as 20 years 35 years with good knowledge of 4 people (11.4%) and poor knowledge of 28 people (80.0%). Most of the known husband's support for pregnant women in PMB Azimah, Jambi City who are at risk is categorized as negative, with 6 people (17.1%) having good knowledge and 16 people (45.7%) with poor knowledge. The Chi-Square test results obtained a value of p = 0.017 for mother's age, p = 0.039 for husband's support. The conclusion of this research is that there is a relationship between age and husband's support for pregnant women on the prevention of baby blues in PMB Azimah, Jambi City. It is recommended as reference material and as a reference in further research on the same topic, but with different variables and research locations.